PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI DI BEI - M Wanti Ernita Sianturi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The purpose of this study was to determine the effect of solvabilitas financial ratios, activity and profitability of the company measured by value (Tobin's q) at manufacturing consumer goods industry sector on Indonesia Stock Exchange. Tthis study using a quantitative approach methode. While the types of data used is secondary data. The population used in this study is a company manufacturing consumer goods industry sector in Bursa Efek Indonesia period of 2010-2013. By using purposive sampling techniques or methods to obtain samples. The samples used were 24 companies from 36 industry sectors consumer goods companies that went public during the observation period of 4 years. Data collection method used is the technique of documentation and technical literature. The analytical tool used is multiple linear regression and hypothesis testing using T partially, F test simultaneously and test the coefficient of determination while testing for the model using the classic assumption test results showed a variable Solvency significant negative effect on Tobin's q (t = -2.957; Sig = 0.004) while the variable Activities no significant effect on Tobin's q (t = 0.096; Sig = 0.923) and for the variable profitability showed a positive influence and significant impact on Tobin's q (t = 12.364; Sig = 0.000). F test results indicate that the variable Solvency, Activity and Profitability simultaneously affect the Tobin's q (F count = 57.767; Sig = 0.000). So, the final equation of research results is Y = -1.570 - 0.191 X1 + 0.009 X2 + 0.659 X3 + ei.